2018
DOI: 10.1021/acsomega.7b01521
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Airflow Rate Modulates Toxicant Profiles and Can Lead to Concerning Levels of Solvent Consumption

Abstract: Electronic cigarettes enabling enhanced airflow have grown in popularity in recent years. The objective of this study is to show that flow rates modulate the levels of specific aerosol toxicants produced in electronic cigarettes. Flow rates used in various laboratory investigations involving e-cigarettes have varied widely to date, and can thus promote interlaboratory variability in aerosol product profiles. The thermal decomposition of hydroxyacetone and glycolaldehyde is less favorable at lower temperatures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 47 publications
2
67
0
Order By: Relevance
“…Our results with the top-coil e-cigarette were consistent with previous reports. Previous studies showed decreased total particle mass concentration [36] and carbonyl emissions [17] at higher flow rates using cig-a-like, top-coil, bottom-coil, and JUUL devices. Faster air flows through the heating chamber were shown to decrease coil temperature [16], leading to lower aerosol and carbonyl emissions.…”
Section: Effect Of Vaping Topography On E-cigarette Emissionsmentioning
confidence: 86%
See 3 more Smart Citations
“…Our results with the top-coil e-cigarette were consistent with previous reports. Previous studies showed decreased total particle mass concentration [36] and carbonyl emissions [17] at higher flow rates using cig-a-like, top-coil, bottom-coil, and JUUL devices. Faster air flows through the heating chamber were shown to decrease coil temperature [16], leading to lower aerosol and carbonyl emissions.…”
Section: Effect Of Vaping Topography On E-cigarette Emissionsmentioning
confidence: 86%
“…yields were shown to increase with puff duration, while puff flow rate had no effect [14]. E-liquid consumption and emissions of some carbonyls were observed to depend on puff flow rate [17].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…It is well established that e-cig users try to avoid dry puffs, which occur in dry burn conditions. This vaping condition is related to the formation of high levels of aldehydes, including formaldehyde, a known carcinogen and respiratory toxicant 13,30 . Therefore, ensuring that this condition is avoided during the exposures is crucial.…”
mentioning
confidence: 99%